Control and Administration of Weight and Measures in the Cities of the Roman Empire ("Pars Occidentalis") - Pérez Zurita, Antonio D. (Gerión. Revista de Historia Antigua, 2012)
In this paper, we examine how members of the Roman administration controlled and managed the weight and measure systems, both in the Urbs and in various towns and colonies in the Western Empire. We examine which magistrates were in charge of this task and the powers assigned to them. Similarly, we assess the expansion these measurement tools reached, how they were financed, as well as the methods used and the participation of various governmental authorities in their standardization and implementation at the local level. Finally, we study the spatial context in which these tools were located.
Keywords: Rome; cities; public administration; institutions; weights and measures.